Phytophthora sojae Pathotype Distribution and Fungicide Sensitivity in Michigan - McCoy, Austin G (Plant disease, 2022)
Identifying the pathotype structure of a Phytophthora sojae population is crucial for the effective management of Phytophthora stem and root rot of soybean (PRR). P. sojae has been successfully managed with major resistance genes, partial resistance, and fungicide seed treatments. However, prolonged use of resistance genes or fungicides can cause pathogen populations to adapt over time, rendering resistance genes or fungicides ineffective. A statewide survey was conducted to characterize this pathotype structure and fungicide sensitivity of P. sojae within Michigan. Soil samples were collected from 69 fields with a history of PRR and fields having consistent plant stand establishment issues. Eighty-three isolates of P. sojae were obtained, and hypocotyl inoculations were performed on 14 differential soybean cultivars, all of which carry a single Rps gene or no resistance gene. The survey identified a loss of effectiveness of Rps genes 1b, 1k, 3b, and 6, compared with a previous survey conducted in Michigan from 1993 to 1997. Three effective resistance genes were identified for P. sojae management in Michigan; Rps 3a, 3c, and 4. Additionally, the effective concentration of common seed treatment fungicides to inhibit mycelial growth by 50% (EC50) was determined. No P. sojae isolates were insensitive to the tested chemistries with mean EC50 values of 2.60 × 10-2 μg/ml for ethaboxam, 3.03 × 10-2 μg/ml for mefenoxam, 2.88 × 10-4 μg/ml for oxathiapiprolin, and 5.08 × 10-2 μg/ml for pyraclostrobin. Results suggest that while there has been a significant shift in Rps gene effectiveness, seed treatments are still effective for early season management of this disease